Free nitrous acid pretreatment of sludge to achieve nitritation: The effect of sludge concentration. (August 2019) - Wang, Zenghua; Wang, Bo; Gong, Xiaofei; Qiao, Xin; Peng, Yongzhen
Graphical abstract: Highlights: Sludge concentration affected FNA pretreatment performance. Flocs sizes declined and more EPS was released to resist FNA inactivation. FNA/MLVSS was used to characterize FNA intensity relative to sludge concentration. FNA/MLVSS is more valuable than solely FNA as a criterion for inhibiting NOB. FNA/MLVSS increment favors the achievement of nitritation in a range of 0.16–0.30. Abstract: This study investigated the effect of sludge concentration (expressed by mixed liquor volatile suspended solids, MLVSS) on free nitrous acid (FNA) pretreatment strategy to achieve nitritation. Results showed when FNA was 0.308 mgHNO2 -N/L, nitrite oxidizing bacteria (NOB) activity increased by 70.2% as MLVSS increased from 8.4 to 16.8 g/L. Nitrite accumulation ceased as MLVSS increased to 12.6 g/L, indicating that FNA inhibition of NOB gradually weakened with increasing MLVSS. When FNA was higher than 0.770 mgHNO2 -N/L, NOB activity was completely inhibited and the effect of MLVSS on FNA inhibition was negligible, with nitrite accumulation potential (NAP) varying from 88.1% to 90.0%. Mechanism investigation demonstrated flocs sizes distinctly declined, with more extracellular polymeric substances (EPS) released to resist FNA inactivation. Linear fitting showed NAP increased with FNA/MLVSS increment. Therefore, MLVSS affected FNA pretreatment performance, with FNA/MLVSS proposed as a more valuable criterion in FNA pretreatment strategy development, than the solely FNA.